Analisis Dampak Pembelajaran Mata Kuliah Prodi Perbankan Syariah STES Bhakti Nugraha terhadap Minat Menabung Mahasiswa di Bank Syariah - Muhammad Fahyudin; Ade Marpudin; Hermawan Timbas (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2022)
The purpose of this study is to examine the influence of Islamic banking study program courses at STES Bhakti Nugraha Tangerang on the desire to use Islamic banking products and services. To achieve this objective, this study employs a qualitative descriptive research approach in which data in the form of phenomena, words from interviews, and opinion poll questions are analyzed and verified using qualitative data analysis techniques. This study focuses on STES Bhakti Nugraha Tangerang City seventh-semester students. On the basis of interviews, observations, and opinion polls, it was determined that STES Bhakti Nugraha semester VII students comprehend what they are learning in the Islamic banking study program and believe that learning outcomes can affect their desire to use Islamic banking services. Those who use Islamic banking are nearly identical to those who use conventional banking services, according to another finding. This is a result of the simplicity with which conventional banks provide their services.